TEACHER’S PROFESSIONALISM AND ITS IMPLICATION ON STUDENT’S LEARNING ACHIEVEMENT IN GORONTALO - Muh. Arif; Munirah Munirah (Jurnal Al-Ilmi: Jurnal Riset Pendidikan Islam, 2021)
This research investigated teacher professionalism in improving learning achievement at al-Falah Islamic Boarding School in Gorontalo. It can be seen from the planning of learning such us formulation of learning objectives, determination of evaluation tools, determination of learning activities, and determination of methods and learning tools. In the implementation of learning in the form of delivering learning material, learning methods, media or learning tools, and learning interactions. Furthermore, the learning assessment used by teachers is assignments or homework and daily tests. The result of this research was that teacher professionalism has positive implications for students' learning achievement at al-Falah Islamic Boarding School in Gorontalo.